1996
DOI: 10.1007/bf00034782
|View full text |Cite
|
Sign up to set email alerts
|

P680+ reduction in oxygen-evolving Photosystem II core complexes

Abstract: The kinetics of P680(+) reduction in oxygen-evolving spinach Photosystem II (PS II) core particles were studied using both repetitive and single-flash 830 nm transient absorption. From measurements on samples in which PS II turnover is blocked, we estimate radical-pair lifetimes of 2 ns and 19 ns. Nanosecond single-flash measurements indicate decay times of 7 ns, 40 ns and 95 ns. Both the longer 40 ns and 95 ns components relate to the normal S-state controlled Yz → P680(+) electron transfer dynamics. Our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
20
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
8
20
1
Order By: Relevance
“…As found in single flash measurements (Lukins et al 1996), the major time constants required to describe the decay are 7, 40 and 95 ns, 4 and 90 #s. With UV irradiation, the core complexes show a progressive decrease in the total signal amplitude, and a fast decrease in the nanosecond region of the 830 nm absorbance signal with a concomitant increase in the microsecond contribution ( Figure 2). Multiexponential non-linear least squares fitting of the transients allowed comparison of the effect of UV irradiation on the amplitudes of these time constants (Figure 3), after checking that these were the optimal time constants using curve fitting methods described in Lukins et al (1996). In addition, UV irradiation caused the appearance and rapid increase of one new component not present in control samples which had a time constant of 10 #s. This component was clearly distinguished in the curve fitting analysis from the 4 #s component present in control samples, and in the case of samples irradiated for 5 min both components needed to be included for a good fit.…”
Section: Repetitive Flash-induced Absorbance Change Measurementssupporting
confidence: 56%
See 2 more Smart Citations
“…As found in single flash measurements (Lukins et al 1996), the major time constants required to describe the decay are 7, 40 and 95 ns, 4 and 90 #s. With UV irradiation, the core complexes show a progressive decrease in the total signal amplitude, and a fast decrease in the nanosecond region of the 830 nm absorbance signal with a concomitant increase in the microsecond contribution ( Figure 2). Multiexponential non-linear least squares fitting of the transients allowed comparison of the effect of UV irradiation on the amplitudes of these time constants (Figure 3), after checking that these were the optimal time constants using curve fitting methods described in Lukins et al (1996). In addition, UV irradiation caused the appearance and rapid increase of one new component not present in control samples which had a time constant of 10 #s. This component was clearly distinguished in the curve fitting analysis from the 4 #s component present in control samples, and in the case of samples irradiated for 5 min both components needed to be included for a good fit.…”
Section: Repetitive Flash-induced Absorbance Change Measurementssupporting
confidence: 56%
“…Flash-induced 830 nm absorbance changes were measured using the apparatus described in Lukins et al 1996. Measurements were made with the sample being excited repetitively at 2 Hz or, in the case of monitoring the S-state dependence, with a series of 5 flashes at 20 Hz of green (532 nm) light from a pulsed frequencydoubled Nd:YAG laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation energy was very low, about 10 kJ mol -1 (37,38). Taking the gross kinetical ruler of Moser et al (82) at face value and using the observed rate of electron transfer between Y Z and P 680 + , about 5 × 10 7 s -1 in oxygen-evolving PSII (8,37,(83)(84)(85)(86), we calculated a reorganization energy of about 0.5 eV (123,124). An even higher reorganization energy, 0.7 eV, has been obtained, for instance, for the electron transfer (in ∼200 ps) from bacteriopheophytin to Q A in the bacterial reaction center (see ref 82 and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1c shows the photoelectric response of pro teoliposomes containing PSII core complexes with inac tive OEC. A rapid decline in the photopotential in these preparations seems to be caused by the electron recombi nation between P680 and Q A [28]. Thus, the oxygen evolving activity is probably retained in ~81% of the PSII complexes incorporated into the liposomes.…”
Section: Resultsmentioning
confidence: 95%